Козача Рада як центральний орган керівництва повстанських сил Правобережжя УСРР у 1921-22 роках - Стегній, П. (Схід, 2012)
Стаття присвячена дослідженню питань, пов'язаних із виникненням та діяльністю "Козачої Ради", що була одним із центральних органів керівництва антибільшовицькими повстанськими силами Правобережжя УСРР у 1921-1922 роках. Автор статті детально аналізує суперечності у відомостях про виникнення та діяльність "Козачої Ради" та робить припущення про зв'язок цієї організації з осередками Вільного козацтва та монархічно зорієнтованою частиною української еміграції. The article is devoted to the research of the issues connected with appearance and activities of "Cossacks council" that was one of the central governing body of antibolshevik rebel's forces of the right bank in the USSR in 1921 1922. The author of the article gives a thorough analysis of the discrepancies in the data about formation and activities of "Cossacks council" and makes an assumption about the connection of this organization with Free Cossack centres and the monarchy-oriented part of Ukrainian emigration.